EFFECT OF INTELLECTUAL CAPITAL AND OWNERSHIP STRUCTURE ON FIRM VALUE WITH CSE MEDIATOR - Setiawan, Elizabeth Tanjung; Handoko, Jesica (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2024)
The objective of the study is determining the effect of intellectual capital and ownership structure on firm value through capital structure efficiency (CSE). Intellectual capital is measured using the Value Added Intellectual Coefficient (VAICTM), ownership structures is measured by percentage of managerial ownership and institutional ownership, company value is measured by Price to Book Value (PBV), and capital structure efficiency is measured by interest bearing debt to equity ratio (IBDER). The manufacturing companies registered on the IDX in 2019-2021 are the study objects. The data analysis technique uses multiple linear regression analysis with a path analysis model. The results of the study show that intellectual capital and institutional ownership effect on firm value directly, but managerial ownership has no effect on firm value. Intellectual capital and ownership structure do not affect firm value directly or mediate by capital structure efficiency